Challenging the Philosophical Axis Enactment in the Sustainability of Malioboro Street Vendors’ Relocation - Kardanardi, Lucky; Syahdani, Muwalliha (Center for Southeast Asian Social Studies (CESASS), 2023)
In enacting its